Respuesta :

Answer:

  1/6^3

Step-by-step explanation:

The applicable rules of exponents are ...

  a^-b = 1/a^b

  (a^b)(a^c) = a^(b+c)

__

Your expression can be simplified as follows:

  [tex]\dfrac{6^{-5}}{6^{-2}}=\dfrac{1}{(6^{-2})(6^5)}=\dfrac{1}{6^{-2+5}}=\boxed{\dfrac{1}{6^3}}[/tex]

_____

Additional comment

If you think of an exponent as signifying repeated multiplication, the rules of exponents may be easier to remember. The exponent tells you how many times the base is a factor in the product.

Consider multiplication:

  [tex](x\cdot x\cdot x)\cdot(x\cdot x)=x^3\cdot x^2=x^{3+2}=x^5\\\\(x\cdot x\cdot x)\cdot(x\cdot x\cdot x)=(x^3)^2=x^{3\cdot2}=x^6[/tex]

Consider division:

  [tex]\dfrac{x\cdot x\cdot x}{x\cdot x}=x\quad\Longleftrightarrow\quad\dfrac{x^3}{x^2}=x^{3-2}=x^1\\\\\dfrac{x\cdot x}{x\cdot x\cdot x}=\dfrac{1}{x}\quad\Longleftrightarrow\quad\dfrac{x^2}{x^3}=x^{2-3}=x^{-1}[/tex]

This may help you see that a positive exponent in the denominator is equivalent to a negative exponent in the numerator (and vice versa).

ACCESS MORE